2016
DOI: 10.1002/ijc.30431
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation changes measured in pre‐diagnostic peripheral blood samples are associated with smoking and lung cancer risk

Abstract: DNA methylation changes are associated with cigarette smoking. We used the Illumina Infinium HumanMethylation450 array to determine whether methylation in DNA from pre‐diagnostic, peripheral blood samples is associated with lung cancer risk. We used a case‐control study nested within the EPIC‐Italy cohort and a study within the MCCS cohort as discovery sets (a total of 552 case‐control pairs). We validated the top signals in 429 case‐control pairs from another 3 studies. We identified six CpGs for which hypome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 27 publications
6
133
0
Order By: Relevance
“…Several epigenome-wide studies have consistently shown that the methylation levels of AHRR and F2RL3 were the top-ranked signals associated with tobacco smoking [7, 10] and smoking-related health risks such as lung cancer[11, 12] or cardiovascular disease[13]. Therefore, in the present study, we aimed to validate the previously identified association of the methylation levels of those genes with smoking.…”
Section: Introductionmentioning
confidence: 72%
“…Several epigenome-wide studies have consistently shown that the methylation levels of AHRR and F2RL3 were the top-ranked signals associated with tobacco smoking [7, 10] and smoking-related health risks such as lung cancer[11, 12] or cardiovascular disease[13]. Therefore, in the present study, we aimed to validate the previously identified association of the methylation levels of those genes with smoking.…”
Section: Introductionmentioning
confidence: 72%
“…A series of case–control studies nested within the MCCS of breast, colorectal, gastric, kidney, lung, mature B‐cell lymphoma, prostate and urothelial cancer were conducted . Cancer diagnoses were identified by linkage with the Victorian Cancer Registry and the Australian Cancer Database (Australian Institute of Health and Welfare).…”
Section: Methodsmentioning
confidence: 99%
“…A series of case-control studies nested within the MCCS of breast, colorectal, gastric, kidney, lung, mature B-cell lymphoma, prostate and urothelial cancer were conducted. [32][33][34][35] Cancer diagnoses were identified by linkage with the Victorian Cancer Registry and the Australian Cancer Database (Australian Institute of Health and Welfare). For each nested casecontrol study, controls were individually matched to incident cases (diagnosed after blood sample collection) on age using incidence density sampling (i.e.…”
Section: Cancer and Death Ascertainmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the best evidence for the later life effect of the environment on DNA methylation is from Fasanelli and colleagues, who showed (by EWAS) that smoking reversibly caused hypomethylation of the AHRR and FR2L3 genes in adults and that approximately 37% of the total effect of smoking on lung cancer risk is mediated by methylation at these loci [15]. Importantly, these findings have recently been independently replicated [16]. Other EWAS have also shown that genetic predisposition to adult onset phenotypes may be mediated by DNA methylation [17,18].…”
Section: Dna Methylation Marks Integrate Genetic and Environmental Inflmentioning
confidence: 99%